Pengaruh Penerapan Metode Al-Muyasar Terhadap Kemampuan Membaca Al-Qur’an Pada Siswa Kelas Vii Di Mts Ar-Rifa’i Bogor - Nahdiatun Niswah; Muhyani Muhyani; Nurman Hakim (KOLONI, 2024)
The Al-Muyassar method can enable students at MTs Ar-Rifa'i to be able to read the Al-Qur'an fluently and correctly according to recitation. The difference between the al-Muyasar Al-Qur'an reading method and other Al-Qur'an reading methods is that the al-Muyasar learning method is easy, fun and touching. So from this the researcher formulated the problem, namely "Is there a significant influence of al-Muyasar on the ability to read the Al-Qur'an among students at MTs Ar-Rifa'i?" This research aims to determine the influence of Al-Muyassar on the ability to read the Al-Qur 'an on students at MTs Ar-Rifa'i Bogor? This research uses a quantitative approach. And uses a quasi-experiment method which aims to collect data and hypotheses that are in accordance with the theories and concepts that have been collected previously. The ability to read the Al-Quran in the experimental class using the al-Muyasar method increased from an average pre-test score of 60.06 and an average post-test score of 70.51. Judging from the hypothesis test using the t-test (independent-sample t-test), even though the post-test average score for the experimental class is higher than the control class, the hypothesis result is Sig. (2-tailed), 0.078 > 0.05. So Ha is rejected and H0 is accepted. The use of the al-muyasar method based on the results of the t-test (independent sample t-test) found no effect on the ability to read and memorize the Koran using the al-muyasar method in memorizing the Koran at MTs Ar-Rifa'i Bogor. The use of the al-Muyasar method has no effect on learning outcomes as proven by the hypothesis test image with a Sig score (2-tailed), 0.078 which is more than 0.05